Phenotypic Heterogeneity in Tumor Progression, and Its Possible Role in the Onset of Cancer - Deshmukh, Saniya; Saini, Supreet (Frontiers in Genetics, 2020)
Heterogeneity among isogenic cells/individuals has been known for at least 150 years. Even Mendel, working on pea plants, realized that not all tall plants were identical. However, Mendel was more interested in the discontinuous variation between genetically distinct individuals. The concept of environment dictating distinct phenotypes among isogenic individuals was made rigorous by Fisher, however, the implications of this variation in dictating evolutionary fate of populations was not known at that time. In the 100 years since Fisher’s work, phenotypic heterogeneity has been shown to impact evolution of populations in numerous examples at different scales of life. In this review, we discuss how phenotypic heterogeneity and its evolutionary implications exist at all levels of life, from viruses to mammals. In particular, we discuss how a particular disease condition (cancer) is impacted by heterogeneity among isogenic cells, and propose a potential role that phenotypic heterogeneity might play towards onset of the disease.